2014
DOI: 10.1128/jvi.02538-14
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A Targets the DREF Nuclear Factor To Regulate Virus Gene Expression, DNA Replication, and Growth

Abstract: The adenovirus E1A gene is the first gene expressed upon viral infection. E1A remodels the cellular environment to maximize permissivity for viral replication. E1A is also the major transactivator of viral early gene expression and a coregulator of a large number of cellular genes. E1A carries out its functions predominantly by binding to cellular regulatory proteins and altering their activities. The unstructured nature of E1A enables it to bind to a large variety of cellular proteins and form new molecular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
7
28
0
Order By: Relevance
“…Nek9 was found to occupy the E2 early promoter and, to a lesser extent, the E3 promoter, but not E4 nor the major late promoter (MLP). E1A was found on all promoters tested, as previously observed (24). Recruitment of Nek9 to the E2 early promoter correlated with alteration in expression of E2A (Fig.…”
Section: Nek9 Knockdown Reduces Hadv Growthsupporting
confidence: 86%
See 1 more Smart Citation
“…Nek9 was found to occupy the E2 early promoter and, to a lesser extent, the E3 promoter, but not E4 nor the major late promoter (MLP). E1A was found on all promoters tested, as previously observed (24). Recruitment of Nek9 to the E2 early promoter correlated with alteration in expression of E2A (Fig.…”
Section: Nek9 Knockdown Reduces Hadv Growthsupporting
confidence: 86%
“…Analysis of expression data was carried out using the Pfaffl method (26), and the data were normalized to GAPDH (glyceraldehyde-3-phosphate dehydrogenase) mRNA levels and compared between siControl-and siNek9-transfected cells. Primers used for E1B, E2, E3, E4, and hexon were previously described (24). Total E1A was detected with primers binding within exon 2: TCCGGTCCTTCTAACACACC and GGCGTTTACAGCTCAAGTCC, as previously described (27).…”
Section: Antibodiesmentioning
confidence: 99%
“…The NS1 protein of influenza virus prevents caspase-1 activation and the secretion of IL-1b and IL-18 via an unknown mechanism. The IL-1b and IL-18 pathways have been observed to be regulated by the vaccinia virus protein B15R and the molluscum contagiosum poxvirus proteins MC53L and MC54L, which can bind and inhibit IL-1b and IL-18, respectively [132,133]. Thus, the viral alkaline exonuclease of Epstein Barr virus (BGLF5) down-regulates molecules of the immune system such as TLR-2 and CD1 by degrading the mRNAs that encode them [134].…”
Section: Regulation Of the Inflammasomementioning
confidence: 99%
“…Our studies of new C terminus binding proteins have identified DREF (15) and Ku70 (18) as novel E1A interaction partners. Here, we report the identification of another novel E1A C terminus binding protein, RuvBL1 (also known as Pontin and TIP49a).…”
Section: Importancementioning
confidence: 98%
“…Lastly, E1A inhibits histone H2B monoubiquitination by interfering with the RNF20 ubiquitin ligase (14). E1A also interacts with DREF, a component of promyelocytic leukemia protein (PML) bodies that appears to play a role in the innate antiviral response; interference with DREF function by E1A enhances virus growth (15). E4 orf3 is also involved in IFN suppression and inhibition of PML body function and in the immune response (16).…”
Section: Importancementioning
confidence: 99%